Update of the Healthy Eating Index: HEI-2010 - Guenther, Patricia M.; Casavale, Kellie O.; Reedy, Jill; Kirkpatrick, Sharon I.; Hiza, Hazel A.B.; Kuczynski, Kevin J.; Kahle, Lisa L.; Krebs-Smith, Susan M. (Journal of the Academy of Nutrition and Dietetics, 2013)
The Healthy Eating Index (HEI) is a measure of diet quality in terms of conformance with federal dietary guidance. Publication of the 2010 Dietary Guidelines for Americans prompted an interagency working group to update the HEI. The HEI-2010 retains several features of the 2005 version: (a) it has 12 components, many unchanged, including nine adequacy and three moderation components; (b) it uses a density approach to set standards, eg, per 1,000 calories or as a percentage of calories; and (c) it employs least-restrictive standards; ie, those that are easiest to achieve among recommendations that vary by energy level, sex, and/or age. Changes to the index include: (a) the Greens and Beans component replaces Dark Green and Orange Vegetables and Legumes; (b) Seafood and Plant Proteins has been added to capture specific choices from the protein group; (c) Fatty Acids, a ratio of polyunsaturated and monounsaturated to saturated fatty acids, replaces Oils and Saturated Fat to acknowledge the recommendation to replace saturated fat with monounsaturated and polyunsaturated fatty acids; and (d) a moderation component, Refined Grains, replaces the adequacy component, Total Grains, to assess overconsumption. The HEI-2010 captures the key recommendations of the 2010 Dietary Guidelines and, like earlier versions, will be used to assess the diet quality of the US population and subpopulations, evaluate interventions, research dietary patterns, and evaluate various aspects of the food environment.